EDUKASI PENGGUNAAN ALAT PELINDUNG DIRI (APD) UNTUK MENINGKATKAN KESELAMATAN KERJA PADA PEKERJA PROYEK PEMBANGUNAN PERUMAHAN DI KECEMATAN DELI TUA - Ginting, Evfy Septriani (INSTITUT KESEHATAN DELI HUSADA, 2025)
Occupational safety and health (OSH) play a vital role in the construction sector, especially in high-risk housing projects. A major contributing factor to workplace accidents is the lack of worker awareness and adherence to Personal Protective Equipment (PPE) guidelines. To address this issue, this Community Service Program (PkM) is designed to improve workers’ understanding of the significance of PPE through awareness initiatives, training sessions, and practical demonstrations. The program utilizes interactive counseling, PPE simulations, and discussions to tackle implementation challenges. As a result, workers have shown increased knowledge and compliance with PPE usage, fostering a safer work environment and helping to reduce accident rates in housing construction projects.